2009
DOI: 10.4129/ifm.2009.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Strategie di gestione del rapporto cervo-foresta nel Parco Nazionale delle Foreste Casentinesi, Monte Falterona e Campigna

Abstract: che il Parco Nazionale è chiamato a garantire tra le foreste, spesso di origine direttamente antropica, e la componente faunistica richiede un approccio complesso che non si può limitare a questi due «soggetti» ma che anzi deve esaminare la questione anche alla luce delle dinamiche socioeconomiche del territorio, non temendo di mettere in discussione alcuni presupposti fino ad ora ritenuti irrinunciabili. L'azione del Parco Nazionale mira quindi ad affrontare il problema agendo certamente sulle popolazioni ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…In our study area, S. schaefferi feeds mainly on wild boar, badger, and red deer feces. Moreover, as reported for other areas in northeastern Italy (Melloni 2003), individuals in the study area in previous years were also observed feeding on red fox and horse feces, while fallow deer feces were not utilized (Rizzotto and Barbero 2016). Prasse (1957a) found that, under laboratory conditions, pig feces were not suitable for S. schaefferi, although our research showed that wild boar feces are the most utilized food source.…”
Section: Discussionsupporting
confidence: 72%
“…In our study area, S. schaefferi feeds mainly on wild boar, badger, and red deer feces. Moreover, as reported for other areas in northeastern Italy (Melloni 2003), individuals in the study area in previous years were also observed feeding on red fox and horse feces, while fallow deer feces were not utilized (Rizzotto and Barbero 2016). Prasse (1957a) found that, under laboratory conditions, pig feces were not suitable for S. schaefferi, although our research showed that wild boar feces are the most utilized food source.…”
Section: Discussionsupporting
confidence: 72%